Uji Efek Pemberian Antibakteri ekstrak Daun Kitolod (Isotoma Longiflora (L) Presl.) terhadap Staphylococcus Aureus - Retno Mareintika (Yayasan Pendidikan Medika Indonesia, 2021)
Antibacterial is a substance that can inhibit or kill infectious pathogenic bacteria. Infection is caused by pathogenic bacteria that enter and multiply in body tissues. Bacterial conjunctivitis is caused by one of the most common bacteria with varying degrees of staphylococcus aureus. Kitolod has bioactive substances such as alkaloids, flavonoids, and saponins. The higher the concentration value of kitolod leaf juice (Isotoma longiflora), the higher the inhibition of the growth of Staphylococcus aureus bacteria, namely at a concentration of 100% with an inhibitory power of 17,18333 mm. The purpose of this research method is to determine the effect of giving Kitolod Leaves to conjunctivitis caused by Staphylococcus Aureus. The method used in conducting this research is literature review from various national and international journals. From several studies, it was found that there was an effect of giving Antibacterial extract of Kitolod Leaf (Isotoma Longiflora (L) Presl.) against Staphylococcus Aureus